Overview of research on agricultural robot in China - Libin, Zhang; Qinghua, Yang; Guanjun, Bao; Yan, Wang; Liyong, Qi; Feng, Gao; Fang, Xu (International Journal of Agricultural and Biological Engineering, 2008)
As the representation of new concept agricultural machinery, agricultural robots possess great advantages of improving agricultural productivity, enhancing production environment and solving the problem of labor shortage. Therefore, the strategy of application of agricultural robots and precise agriculture to improve the intelligence and information level of agriculture is the inevitable trend for China’s agriculture of twentieth century. Based on the development status of agricultural robots in China, the agricultural robots are categorized and the performances, structures and characteristics of various agricultural robots such as vegetable grafting robot, transplant robot, mowing robot, spraying robot, harvesting robot are amply introduced. It can be seen that vegetable grafting robot, spraying robot and harvesting robot have already been put into production while others are still at experimental stage. At present, there are several problems such as low popularization, great limitations, high cost and low intelligence, which greatly restrict the development of agricultural robot in China. Thus, open agricultural robot system with good expansibility, generality and flexibility shall be developed and adopted to decrease its cost and shorten the development cycle of robot. The mechanical structure of robot should also be designed as simple as possible. Finally, multi-robot system would become another important development direction of agricultural robot in future. Keywords: agricultural robots; robots for facility breeding; robots for field management; robots for harvesting; robots for grading and detecting DOI: 10.3965/j.issn.1934-6344.2008.01.012-021 Citation: Zhang Libin, Yang Qinghua, Bao Guanjun, Wang Yan, Qi Liyong, Gao Feng, et al. Overview of research on agricultural robots in China. Int J Agric & Biol Eng. 2008;1(1): 12